Karakterisasi material mesopori Ni/MCM-41 dan pengaruh penambahan logam nikel terhadap tingkat keasaman material - Soenandar Milian Tompunu Tengker; Jenny Kumajas (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
Mesoporous material MCM-41 cannot be used directly as a catalyst, so need to be added metals or nonmetals to create an acidic site. Nickel is a Lewis acid metal because it is able to accept lone pairs of electrons from ligands to form complex compounds. The purpose of this study was to produce mesoporous material Ni/MCM-41 and to see the effect of the addition Nickel metal to the acidity level of mesoporous material Ni/MCM-41.Tthe ion exchange method is used to produce Ni/MCM-41 and the gravimetric method to test the acidity of the material. The MCM-41 used for Ni/MCM-41 synthesis has an x-ray diffraction pattern with a hexagonal structure that is identical with the MOC researchers results. BET results is showed the type IV of the Langmuir adsorption isotherm with a surface area of ​​Ni/MCM-41 material 775.9 m2/g, pore volume 0.81 cc/g and pore radius 15.2 Å. TEM characterization shows the morphological shape of Ni/MCM-41 in the form of hexagonal structure. The acidity test results of Ni/MCM-41 material have a higher acidity level compared to MCM-41. Based on the research data, it can be concluded that Ni/MCM-41 has a morphological form with a hexagonal structure, has a large surface area and has a pore size classified as mesoporous material and has a higher acidity level than the MCM-41 synthesized.